2011
DOI: 10.4028/www.scientific.net/kem.487.238
|View full text |Cite
|
Sign up to set email alerts
|

Study on Compound Machining of Polyurethane Polishing Pad and Cluster Abrasive Brush Based on MR Effect

Abstract: Method of compound machining is used to process single crystal silicon and SrTiO3 ceramic substrates, and the factors on effects of compound machining are studied such as magnetic field intensity, processing time, rotating speed of lapping plate and lapping pressure. The results show that the roughness of work pieces processed by compound machining are smaller than that by lapping based on cluster MR effect and polyurethane pad polishing process, while the material removal rate is higher than polyurethane pad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A regional ultra-smooth planarization surface of STO substrate where a surface roughness of Ra being 3.8 nm (Mahr), rms 0.973 nm (Veeco interferometer) was obtained. Li et al [22] used a compound machining method to process STO ceramic substrates, and then studied the effects that compound machining had on the intensity of the magnetic field, the processing time, and the rotating speed of the lapping plate and the lapping pressure. Their results showed that workpieces processed by compound machining are smoother than lapping based on the cluster MR effect and polishing with a polyurethane pad, although more material can be removed than by polishing with a polyurethane pad.…”
Section: Introductionmentioning
confidence: 99%
“…A regional ultra-smooth planarization surface of STO substrate where a surface roughness of Ra being 3.8 nm (Mahr), rms 0.973 nm (Veeco interferometer) was obtained. Li et al [22] used a compound machining method to process STO ceramic substrates, and then studied the effects that compound machining had on the intensity of the magnetic field, the processing time, and the rotating speed of the lapping plate and the lapping pressure. Their results showed that workpieces processed by compound machining are smoother than lapping based on the cluster MR effect and polishing with a polyurethane pad, although more material can be removed than by polishing with a polyurethane pad.…”
Section: Introductionmentioning
confidence: 99%